Impact of phosphorus application on drought resistant responses of Eucalyptus grandis seedlings. Issue 4 (9th January 2019) - Tariq, Akash; Pan, Kaiwen; Olatunji, Olusanya A; Graciano, Corina; Li, Zilong; Li, Ningning; Song, Dagang; Sun, Feng; Wu, Xiaogang; Dakhil, Mohammed A.; Sun, Xiaoming; Zhang, Lin
Abstract : Eucalyptus grandis is the most widely planted tree species worldwide and can face severe drought during the initial months after planting because the root system is developing. A complete randomized design was used to study the effects of two water regimes (well‐watered and water‐stressed) and phosphorus (P) applications (with and without P) on the morphological and physio‐biochemical responses of E. grandis . Drought had negative effects on the growth and metabolism of E. grandis, as indicated by changes in morphological traits, decreased net photosynthetic rates ( P n ), pigment concentrations, leaf relative water contents (LRWCs), nitrogenous compounds, over‐production of reactive oxygen species (ROS) and higher lipid peroxidation. However, E. grandis showed effective drought tolerance strategies, such as reduced leaf area and transpiration rate ( E ), higher accumulation of soluble sugars and proline and a strong antioxidative enzyme system. P fertilization had positive effects on well‐watered seedlings due to improved growth and photosynthesis, which indicated the high P requirements during the initial E. grandis growth stage. In drought‐stressed seedlings, P application had no effects on the morphological traits, but it significantly improved the LRWC, P n, quantum efficiency of photosystem II ( F v /F m ), chlorophyll pigments, nitrogenous compounds and reduced lipid peroxidation. P fertilization improved E. grandis seedling growth under well‐watered conditions but also ameliorated some leaf physiological traits under drought conditions. The effects of P fertilization are mainly due to the enhancement of plant N nutrition. Therefore, P can be used as a fertilizer to improve growth and production in the face of future climate change.